Genshin's Ōjōyōshū and the Construction of Pure Land Discourse in Heian Japan - Rhodes, Robert F. (Pure Land Buddhist Studies, 2017)
The Ōjōyōshū, written by the monk Genshin (942-1017), is one of the most important texts in the history of Japanese religions. It is the first comprehensive guide to the doctrine and practice of Pure Land Buddhism written in Japan and so played a pivotal role in establishing this form of Buddhism in the country. In Genshin's Ōjōyōshū and the Construction of Pure Land Discourse in Heian Japan, the first book in English on the Ōjōyōshū in more than forty years, Robert Rhodes draws on the latest scholarship to shed new light on the text, its author, and the tumultuous age in which it was written.Rhodes begins by providing substantial discussion on the development of Pure Land Buddhism before the Ōjōyōshū's appearance and a thorough account of Genshin's life, the full details of which have never before been available in English.